Reliability and Efficiency of Pitch-Shifting Plug-Ins in Voice and Hearing Research. - Yüksel, Mustafa (Journal of Speech, Language & Hearing Research, 2022)
Purpose: Auditory feedback perturbation with voice pitch manipulation has been widely used in previous studies. There are several hardware and software tools for such manipulations, but audio plug-ins developed for music, movies, and radio applications that operate in digital audio workstations may be extremely beneficial and are easy to use, accessible, and cost effective. However, it is unknown whether these plug-ins can perform similarly to tools that have been described in previous literature. Hence, this study aimed to evaluate the reliability and efficiency of these plug-ins. Method: Six different plug-ins were used at +1 and −1 st pitch shifting with formant correction on and off to pitch shift the sustained /ɑ/ voice recording sample of 12 healthy participants (six cisgender males and six cisgender females). Pitch-shifting accuracy, formant shifting amount, intensity changes, and total latency values were reported. Results: Some variability was observed between different plug-ins and pitch shift settings. One plug-in managed to perform similarly in all four measured aspects with well-known hardware and software units with 1-cent pitch-shifting accuracy, low latency values, negligible intensity difference, and preserved formants. Other plug-ins performed similarly in some respects. Conclusions: Audio plug-ins may be used effectively in pitch-shifting applications. Researchers and clinicians can access these plug-ins easily and test whether the features also fit their aims.